Critical reading research and its implications for critical reading skills for Indonesian language teachers: A systematic literature review - Setiawan, Arif; Hang, Nguyen Thi Thu; Fauzan, Fauzan; Derana, Ganes Tegar (Universitas Ahmad Dahlan, 2023)
The abundance of information sources is the result of rapid technological advances. Rapid technological advances must be balanced with reading skills, one of which is critical reading skills used to filter information sources. This systematic literature review aims to compare the findings of research articles published by the Science and Technology Index (SINTA). The keyword used to find articles in the SINTA database is